Analysis of the Psychometric Properties of the Siblings’ Experience Quality Scale for Individuals with Siblings with Special Needs: 12-18-Year-Old Adolescents Form - Tugba Ozdemir; Murat Bektaş; Gülendam Karadağ (Sakarya Tıp Dergisi, 2025)
Objective: This study was conducted to perform the Turkish validity and reliability study of the siblings’ experience quality scale (SEQS) for healthy siblings who were aged between 12 and 18 and had a sibling with special needs. Materials and Methods: Our study was carried out with healthy siblings of students enrolled in two special education and application schools in a province in the west of Türkiye. Validity and reliability stages were carried out, and experts were consulted. Shapiro-Wilk normality test, content validity index, Pearson correlation analysis, Cronbach’s Alpha coefficient, confirmatory factor analysis, McDonald’s omega test, and t-test were employed in the analysis. Results: Of the participants, 59% were female, 58% had high school education, and 63% had siblings with intellectual disabilities. The mean age of the participants was 14.87±2.06. The scale explained 58.8% of the total variance. It was found that the omega reliability coefficient for the overall scale was 0.85 and that the fit indices obtained as a result of CFA were X2=262.28, df=128, X2/df=2.04, RMSEA=0.073, GFI=0.88, IFI=0.89, NFI=0.80, TLI=0.86, CFI=0.88, RFI=0.76, and AGFI=0.843. The Turkish version of the SEQS was proven to be reliable and valid for the 12-18 age group.Conclusion: The Turkish version of the SEQS was proven to be reliable and valid for the 12-18 age group.